2001
DOI: 10.1128/jb.183.7.2265-2272.2001
|View full text |Cite
|
Sign up to set email alerts
|

Global Impact of sdiA Amplification Revealed by Comprehensive Gene Expression Profiling of Escherichia coli

Abstract: In Escherichia coli the amplification of sdiA, a positive activator of ftsQAZ, genes that are essential for septation, results in mitomycin C resistance. To help us understand this resistance phenotype, genes whose expression was altered by increased sdiA dosage were identified using a DNA microarray-based, comprehensive transcript profiling method. The expression of 62 genes was reduced by more than threefold; of these, 41 are involved in motility and chemotaxis. Moreover, the expression of 75 genes, 36 of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
99
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(108 citation statements)
references
References 23 publications
8
99
0
1
Order By: Relevance
“…However, these acrAB induction rates are low (about twofold increase), probably because of the semi-constitutive expression of acrAB caused by the leakiness of AcrR control. SdiA overexpression also increases the transcriptional level of acrA in addition to that of acrD (Wei et al, 2001). Furthermore, it has been reported that carbonyl cyanide m-chlorophenylhydrazone (CCCP), 2,4-dinitrophenol, tetrachlorosalicylanilide (TCS) and nalidixic acid upregulate the expression of emrAB, via the action of the EmrR repressor protein (Lomovskaya et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…However, these acrAB induction rates are low (about twofold increase), probably because of the semi-constitutive expression of acrAB caused by the leakiness of AcrR control. SdiA overexpression also increases the transcriptional level of acrA in addition to that of acrD (Wei et al, 2001). Furthermore, it has been reported that carbonyl cyanide m-chlorophenylhydrazone (CCCP), 2,4-dinitrophenol, tetrachlorosalicylanilide (TCS) and nalidixic acid upregulate the expression of emrAB, via the action of the EmrR repressor protein (Lomovskaya et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, one of the SOS promoters, uvrY, is found to have a large error (Ϸ45%). This operon has been recently found to participate in a twocomponent signaling system related to stationary-phase response (27,28), and there is evidence that it is regulated by transcription factors other than LexA (29). The relatively large 30% error of polB may hint that it also has slight, as of yet uncharacterized, additional regulation.…”
Section: Detection Of Promoters With Additional Regulationmentioning
confidence: 99%
“…Quantitative real-time reverse transcription-PCR (qRT-PCR) was performed with the Applied Biosystems 7500 real-time PCR system (Applied Biosystems) with cDNA samples from bacteria. Transcription rates of the stxA 2e gene in bacteria were compared to those of the icdA housekeeping gene (51). Primers and TaqMan MGB probes were developed with ABI Prism Primer software (Applied Biosystems) and produced by Applied Biosystems (Applera Deutschland, Darmstadt, Germany).…”
Section: Bacteriamentioning
confidence: 99%